Post-History - Flusser, Vilem, 1920-1991 (Book collections on Project MUSE., 2013)
"In Post-History, Vilem Flusser asks the essential question: Is there any room left for freedom in a programmed world? Written as a series of lectures to be delivered at universities in Brazil, Israel, and France, this first English translation of Post-History brings to an anglophone readership Flusser's first critique of apparatus as the aesthetic, ethical, and epistemological model of present times."--Provided by publisher.